Farmers' reasons for owning small ruminants in a case study of small ruminant production and marketing in the semi-humid zone of Kaloleni Division, Coast Province - Otieno, L.; Ackello-Ogutu, A.C.; Mullins, G.; Reynolds, L. (Small Ruminant Collaborative Research Support Program, 1993)
The average flock size was 10 in 76 households. Flocks were established through purchase from fellow farmers. Sale for cash need was the farmers' main reason for keeping small ruminants. Periods of food deficit in the household were closely linked to the seasonality of cash need. producer household consumption of small ruminant meat was mainly limited to the festive season.